Exhumation of high-pressure granulites of the Guaxupe Complex, southeastern Brazil - Del Lama, E. A.; Zanardo, A.; Oliveira, MAF; Morales, N. (Wiley-Blackwell, 2000)
This paper describes tectonic and metamorphic features of Precambrian rocks from the Guaxupe Complex and Varginha Shear Zone (VSZ) near the city of Guaxupe in the southern part of the Sao Francisco Craton, southeastern Brazil. The VSZ separates the metasediments of Araxa Group to the north from the granulites of Guaxupe Complex to the south. The sinistral transcurrent VSZ crosses the entire area striking approximately E-W, bending towards SE in the eastern part. Because of this bend, transpressional movement occurred, facilitating the exhumation of the garnet-rich rocks of the deepest exposed part of the granulite-facies terrane.In the garnet granulites the highest pressure-temperature conditions recorded are approximately 1040 degreesC and 14.4 kbar. The rocks underwent decompression from 14.0 kbar to 8.0 kbar, cooling from 980 degreesC to 710 degreesC, the retrograde path following the boundary between the kyanite and sillimanite stability fields. This interval is interpreted to record the uplift of the lower crustal granulite-facies terrane and re-equilibration during magmatic intrusions. For the felsic granulites an interval of 700-810 degreesC and 8.0-11.5 kbar was attained, also pointing to regional decompression.The granulites of the Guaxupe Complex comprise a medium- to high-pressure lower-crustal terrane, with local occurrences of higher-pressure garnet-rich gneisses, which were uplifted along a transpressional segment of the VSZ. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: thermobarometry; garnet granulite; transpression; Guaxupe Complex; precambrian; Varginha Shear Zone; Brazil